2015
DOI: 10.1111/ggi.12505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a postoperative outpatient pulmonary rehabilitation program on physical activity in patients who underwent pulmonary resection for lung cancer

Abstract: Two months after lung resection surgery, patients had not recovered to the preoperative PAL. However, compared with the control group, there was an improvement in the postoperative PAL in patients, including older patients, who underwent outpatient pulmonary rehabilitation. Geriatr Gerontol Int 2016; 16: 550-555.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…This corroborates findings from a similar study that did not provide pain management or psychosocial support, and that did not even find improvement in the 6MWT results compared to those in controls [50]. Another study found that postoperative pulmonary rehabilitation alone does improve physical activity, but not to the patients' preoperative baseline [51]. These findings suggest that when disease is detected late, postoperative rehabilitation interventions may be less effective.…”
Section: Rehabilitation Interventions For Lung Cancer: a Changing Rolsupporting
confidence: 82%
“…This corroborates findings from a similar study that did not provide pain management or psychosocial support, and that did not even find improvement in the 6MWT results compared to those in controls [50]. Another study found that postoperative pulmonary rehabilitation alone does improve physical activity, but not to the patients' preoperative baseline [51]. These findings suggest that when disease is detected late, postoperative rehabilitation interventions may be less effective.…”
Section: Rehabilitation Interventions For Lung Cancer: a Changing Rolsupporting
confidence: 82%
“…The SGRQ and 6MWD are the most frequently used outcomes to evaluate improvement in QOL and exercise capacity, but many other outcomes have been reported to evaluate PR efficacy, including the incremental shuttle walk test, Chronic Respiratory Questionnaire, and COPD assessment test. 37 In the present retrospective cohort study, we used the SGRQ and 6MWD, because we have used these markers for years in our hospital. Recently, improvement in physical activity has been thought to be a more important outcome of PR for patients with COPD than improvement in exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, the best measuring method for physical activity has not yet been established in patients with COPD. 37 In the present retrospective cohort study, we used the SGRQ and 6MWD, because we have used these markers for years in our hospital. 5 The results might have been different if we had used other outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity was measured before and after the PA program using a three-axis accelerometer (Actimarker EW4800 P-K; Panasonic Electric Works, Osaka, Japan) that was worn at the waist for 5-6 days. 18 The Actimarker collects triaxial acceleration data at 20 Hz, and the standard deviation of the data for 1 min is defined as the mean value of acceleration. The physical activity level (PAL) was calculated as total energy expenditure per 24 h divided by the basal metabolic rate.…”
Section: Measures Of Physical Activity Levelmentioning
confidence: 99%